2020
DOI: 10.3390/ani10101897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging Time on Meat Quality of Longissimus Dorsi from Yunling Cattle: A New Hybrid Beef Cattle

Abstract: The beef aging process is essential for compliance with certain major requisites, such as sensory characteristics for cooking and meat processing. Meat quality analysis of Yunling cattle, a new hybrid beef cattle bred by Chinese researchers, during the aging process, represents a major research gap. To explore Yunling beef initially, indicators associated with meat quality during the aging process of Yunling, Simmental, and Wenshan cattle were measured. In addition, some important economic traits were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The cooking loss of meat is the loss of water during a cooking process. It reflects the ability of meat to retain water during cooking at high temperature and correlates negatively with meat juiciness [ 44 ]. For the meat processing industry, high cooking loss means lower meat yield, affects the appearance of the meat, and is, therefore, an important economic indicator [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cooking loss of meat is the loss of water during a cooking process. It reflects the ability of meat to retain water during cooking at high temperature and correlates negatively with meat juiciness [ 44 ]. For the meat processing industry, high cooking loss means lower meat yield, affects the appearance of the meat, and is, therefore, an important economic indicator [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, [ 47 ] found that aging for 2 and 14 days had no effect on cooking loss and the average was 21.8%. The authors of [ 44 ] reported that cooking losses were lower for beef aged on day 0 than on day 7 ( p < 0.05), with averages of 25.8% and 30.7%, respectively. The higher cooking loss during aging may be due to the denaturation of muscle protein and degradation of certain muscle proteins, such as desmin and troponin T, by postmortem proteolysis, resulting in a decrease in water-holding capacity in aged beef [ 20 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPA, DHA, ∑ n‐3, and ∑ PUFA were decreased while ∑ n‐6, ∑ n‐6: ∑ n‐3, and ∑ SFA were increased after 21 days of ageing. Lipid oxidation could be the possible reason for the steaks' shift in fatty acid composition during ageing (Fan et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Yunling cattle are a composite breed, created by three-way crossbreeding, that are half Brahman, a fourth Murray Grey, and a fourth Yunnan Yellow cattle, which was achieved and developed in Yunnan, China [ 4 ]. Although some studies have shown that Yunling cattle have a good fattening performance, large body size, high meat production, good carcass traits and fatty acid profiles in meat, the detail mechanisms are still unknown [ 5 ]. Thus, further investigations are needed in order to better understand the basis of the formation of these good characteristics in Yunling cattle.…”
Section: Introductionmentioning
confidence: 99%